Real-time determination of kinetics of adsorption of lead(II) onto palm shell-based activated carbon using ion selective electrode - Aroua, M.K.; Leong, S.P.P.; Teo, L.Y.; Yin, C.Y.; Daud, W.M.A.W. (Bioresource Technology, 2008)
In this study, the kinetics of adsorption of Pb(II) from aqueous solution onto palm shell-based activated carbon (PSAC) were investigated by employing ion selective electrode (ISE) for real-time Pb(II) and pH monitoring. Usage of ISE was very appropriate for real-time adsorption kinetics data collection as it facilitated recording of adsorption data at very specific and short time intervals as well as provided consistent kinetics data. Parameters studied were initial Pb(II) concentration and agitation speed. It was found that increases in initial Pb(II) concentration and agitation speed resulted in higher initial rate of adsorption. Pseudo first-order, pseudo second-order, Elovich, intraparticle diffusion and liquid film diffusion models were used to fit the adsorption kinetics data. It was suggested that chemisorption was the rate-controlling step for adsorption of Pb(II) onto PSAC since the adsorption kinetics data fitted both the pseudo second-order and Elovich models well.